Application of Travelling Salesman Problem for Minimizing Travel Distance of a Two-Day Trip in Kuala Lumpur via Go KL City Bus - Wan Nor Ashikin, Wan Ahmad Fatthi; Mea Haslina, Mohd Haris; Kahtan, Hasan (Springer, 2019)
Kuala Lumpur is a cosmopolitan urban centre of Malaysia and has received more than 11 million tourists per year. Tourists usually spend a few days in Kuala Lumpur to visit as many attractions as possible. However, planning such trips can be challenging for tourists who are unfamiliar with the city. Moreover, they are restricted by time and budget constraints. One of the free charter public transports in Kuala Lumpur is the Go KL City Bus. This study aims to assist tourists or travellers (domestic or international) in optimizing their trip around Kuala Lumpur via the Go KL City Bus. A mathematical approach called travelling salesman problem is used to identify the shortest distance between the places of interest. The study proposes a solution on the basis of a two-day tour route for selected tourist attractions in Kuala Lumpur. Results show that the shortest distance of routes for the first and second days are 48.64 km and 46.96 km, respectively. This study aims to promote tourism in Malaysia, thereby contributing to the country’s economic and tourism growth.